Speech Technique and Culture of Bloggers and Journalists - Abdinazarovich, Bazarov Sherali (European Journal of Life Safety and Stability (2660-9630), 2022)
This article describes speech techniques and culture, as well as ways to increase the effectiveness of the speech of bloggers and journalists. The article talks about situations that negatively affect speech effectiveness, communicative qualities of journalists' speech, and ways to improve speech. Reasonable opinions, conclusions and suggestions are given at the end of the article